Implementasi Mesin Cuci Tangan Portable Anti Covid 19 di Pasar Balang – Balang Kelurahan Borongloe Kabupaten Gowae Hand Washing Machines in Balang-Balang Market, Borongloe Village, Gowa Regency - Muhammad Syahid; Jalaluddin -; Rustan Tarakkan; Ahmad Yusran Aminy (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
One of the efforts to prevent the transmission of Covid 19 is washing hands. Washing hands is one of the sanitation efforts by cleaning hands and fingers using water and soap or handrub by humans to be clean and break the chain of germs. Hands are often the agents that carry germs and cause pathogens to pass from one person to another, either by direct contact or indirect contact. Therefore, seeing the urgency of washing hands in an effort to prevent the transmission of Covid 19, we provide assistance to implement hand washing in public facilities where contact between humans often occurs. The service was carried out on October 3, 2020 at the Balang-Balang market, Borong Loe Village, Bonto Marannu District, Gowa Regency. The head of the Borong loe village received hand washing machine assistance. In addition to hand washing machine assistance, information is also displayed regarding proper hand washing steps and information about the spread of covid 19